Smartphone applications for the management of epilepsy in children and adolescents - Gabriela Garcia de Carvalho Laguna; Diego Bastos Ribeiro; Lidhane Santos Coelho; Murilo Sousa Ramos; Karolaine da Costa Evangelista; David Santos Libarino; Davi Tanajura Costa (Sociedade de Pediatria de São Paulo, 2024)
ABSTRACT Objective: To describe how smartphone applications can contribute to the management of epilepsy in children and adolescents. Data source: This is an integrative review conducted on the Medline, PubMed, and SciELO databases, based on the descriptors "epilepsy" and "smartphone." Original studies published between 2017-2023 in Portuguese or English that addressed the research question were included. Theses and dissertations, duplicate studies, literature reviews, and studies that did not answer the research question were excluded. Data synthesis: A total of 178 studies were located, of which six were selected for this review. The sample included 731 participants (631 children and adolescents with epilepsy and 100 caregivers). The applications allow for the collection of seizure frequency; timing and type of crisis; reminders for medication administration; and information about sleep quality. They can store these data for healthcare professionals, caregivers, and users to monitor the progress of the condition. Conclusions: The use of applications in managing seizures in children and adolescents with epilepsy shows promising results by promoting continuous and personalized monitoring. Further studies are needed to optimize beneficial outcomes and overcome challenges.